Spontaneous Neck Hematoma - Bhandari, R; Limbu, TR; Ghimire, A (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 19-20 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6799